Parametric analysis of the factors affecting the efficiency of ground heat exchangers and design application aspects in Cyprus - Pouloupatis, Panayiotis; Tassou, Savvas A.; Christodoulides, Paul; Florides, Georgios A. (My University, 2017)
The objective of this paper is to examine the factors affecting the sizing and positioning of Ground Heat Exchangers (GHEs) in Cyprus. This is achieved through the investigation of the influence of the temperature, thermal conductivity, specific heat and density of the ground as well as pipe diameter on the performance of GHEs using computer software modelling in conjunction with test data. Also, the long term temperature variation of the ground around the boreholes is examined since this affects the positioning of the GHEs. Because of the large number of parameters involved in the design the desired result can be achieved in various ways by considering the specific parameters. The results of the simulations have shown that, generally speaking, the island of Cyprus is suitable for geothermal heat pumps.
Keywords: Borehole; GLD software; Ground heat exchangers; Ground parameters